Time-depth recorders attached to chick-rearing murres in 2005 - Elliott, Kyle H.; Hare, James F.; Le Vaillant, Maryline; Gaston, Anthony J.; Ropert-Coudert, Yan; Anderson, W. Gary (Dryad Digital Repository, 2014)
Raw text files generated by Lotek download software. After a preamble including the logger serial number, the data file presents three columns: the time & date, the temperature in degrees Celsius and the pressure in psi. To convert psi into approximate depth, multiply by 0.705. The text files are organized into folders representing the deployments. Each file name also has the unique eight digit band number of the individual bird to whom the TDR was attached. The band number serves as the identifier to relate it to the meta-data file that includes sex, age and other attributes of the bird.